Evaluation of Serious Adverse Event Reporting Forms for Clinical Trials: A Comparative Korean Study. (December 2020) - Lee, Heeyoung; Park, Cholong; Choi, Jinwon; Jeong, Seongeun; Cho, Hyunin; Huh, Wooseong; Kim, Eunyoung
Safety surveillance, using appropriately consistent review criteria, could improve human participants' well-being in clinical trials. To establish a globally consistent framework, the quality of the current content for review by institutional review boards (IRBs), as mandatory oversight entities, requires evaluation. This study collected and analyzed forms reporting serious adverse events (SAEs) to IRBs/ Research Ethics Committees(RECs) to compare them with the well-structured form presented in the literature using completeness and accuracy scores. We found sub-optimal completeness and accuracy scores when compared with perfect scores ( p < .05). Less than half of the retrieved forms had queries on causality assessment (≤43.1%). Thus, contents of SAE forms require improvement for IRB oversight and, further, there is a need to develop a well-structured form that could improve international consistency.